Method for promoting densification sintering of transition metal boride and improving hardness of transition metal boride by adding trace silicon dioxide

By adding trace amounts of silica during the sintering of transition metal boride, it prompts it to react with B2O3 to form a glass phase, solving the problem of difficulty in densification and sintering of transition metal boride and low hardness, and achieving the improvement of high density and hardness .

CN119430949AActive Publication Date: 2025-02-14GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411468776.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-14
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

During the sintering process, the presence of surface amorphous B2O3 in the transition metal boride leads to difficulty in densification and low hardness.

Method used

By adding trace amounts of silica (SiO2) during the sintering process, it reacts with B2O3 to form a glass phase, promoting densified sintering and increasing the hardness of the transition metal boride.

Benefits of technology

High density sintering and hardness improvement of transition metal borides have been achieved, with a density of 98.36% and a hardness of 24.9±0.48Gpa, which is better than the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005094140060000011
    Figure HDA0005094140060000011
  • Figure HDA0005094140060000012
    Figure HDA0005094140060000012
  • Figure HDA0005094140060000021
    Figure HDA0005094140060000021
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic nonmetal hard materials, and discloses a method for promoting densification sintering of transition metal boride and improving the hardness of the transition metal boride by adding trace silicon dioxide. A small amount of silicon dioxide is added in the transition metal boride preparation process, a B2O3-SiO2 glass phase is synthesized, crystal grains are effectively refined, submicron transition metal boride powder is prepared, the submicron transition metal boride powder has good sintering performance, and transition metal boride ceramics with high density and high hardness can be prepared; the density of the sintered transition metal boride ceramic is 98%, and the transition metal boride ceramic still keeps high hardness under high load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic hard materials, and particularly relates to a method for promoting the densification sintering of transition metal borides and improving their hardness by adding a trace amount of silicon dioxide. Background Art

[0002] Transition metal borides (TMBs), such as WB2 and ZrB2, are considered to be ideal structural materials for extreme environment applications (such as high-temperature nuclear reactors, jet engines, and catalytic materials) due to their high melting point (>3000℃), high hardness, excellent thermal shock resistance, corrosion resistance, and electrocatalytic performance, and can be synthesized at normal pressure. However, even in extreme environments such as high temperature / high pressure or long-term solid-phase sintering, the densification sintering of transition metal borides still faces huge challenges.

[0003] Studies have shown that the surface of transition metal borides is usually covered with a layer of amorphous B2O3 with a nanometer thickness, which melts at 450°C and evaporates at about 1400°C. During high-temperature sintering, this phenomenon will lead to the existence of a liquid phase for a long time, which will cause grain coarsening and a decrease in sintering activity; on the other hand, the volatilization of B2O3 at high temperatures leads to a reduction in boron sources, resulting in a large number of pores on the surface of sintered ceramic samples. These factors may be the main reasons for the difficulty in densification sintering of transition metal borides and their low hardness.

[0004] At present, the measures to solve this problem mainly include the following: (1) Remove the by-product B2O3 by boron thermal reduction combined with water washing process, and prepare ultrafine ZrB2 powder at 1000℃. The density can be increased to about 98% at SPS-2000℃, but this process cannot completely remove B2O3 (oxygen content is 1.98wt%), and the process is relatively complicated and not suitable for large-scale industrial production (Journal of the European Ceramic Society 40(12)(2020)3844-3850. (2) By adding methanol to dilute HF to etch oxide, under optimal corrosion conditions, the oxygen content of ZrB2 can be reduced from 1.23wt% to 0.34wt%, and the density can reach 99.5%. However, this process uses a large amount of chemical reagents, which is not in line with the concept of green production (Journal of Alloys and Compounds 548 (2013) 173-179.). (3) Adding a second phase that can react with B2O3, such as Si3N4, AlN, ZrN, etc., to generate BN and metal oxides, but metal oxides will make it more difficult to densify the composite ceramics. For example, Li et al. added 5Vol% and 10Vol% AlN and prepared ZrB2-15Vol% SiC-AlN ceramics by hot pressing at 1900℃. When the added content was 5Vol% AlN, the sample had a higher density (96.4%). When too much AlN was added, it would react with B2O3 to generate Al2O3, causing holes to appear on the surface of the sample (Journal of Artificial Crystals 38 (S1) (2009) 36-39.).

[0005] The above methods are all based on reducing the oxygen content to achieve densification sintering, but the process is relatively complicated and the residual oxides cannot be completely removed, which affects the densification sintering of ceramics. Therefore, it is urgent to find a method to solve the problem of B2O3 affecting densification sintering. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art that the inevitable amorphous oxide layer B2O3 on the surface of transition metal borides makes it difficult to densify and sinter, thereby affecting the mechanical properties, the primary purpose of the present invention is to provide a method for promoting the densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide; by adding a small amount of silicon dioxide (SiO2), it reacts with B2O3 during the sintering process to form a glass phase, thereby promoting densification sintering, and obtaining a transition metal boride bulk material with higher density and mechanical properties.

[0007] Another object of the present invention is to provide a transition metal boride prepared by the above method.

[0008] Another object of the present invention is to provide an application of the above transition metal boride.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for promoting densification sintering of transition metal borides and improving their hardness by adding a trace amount of silicon dioxide comprises the following steps:

[0011] S1, the following raw materials: silicon dioxide (SiO2) powder, transition metal oxide (TMO S ) powder, boron carbide (B4C) powder, and carbon source powder are weighed and canned under an argon environment, grinding balls are added, and ball milling is performed under an argon protective atmosphere and room temperature to obtain a uniformly mixed powder;

[0012] S2, dry-pressing the uniformly mixed powder obtained in step S1 into a compact by using a dry press, and keeping the temperature at 1300° C. to 1500° C. in a vacuum state for 0.5 to 2 hours, and after cooling with the furnace, grinding and sieving the obtained loose block to obtain transition metal boride (TMBs) powder with added silicon dioxide;

[0013] S3. Put the transition metal boride (TMBs) powder with added silicon dioxide obtained in step S2 into a graphite mold for pre-compression, solidify and sinter by spark plasma sintering at 1500-1700° C. for 5-15 min, and obtain a transition metal boride bulk material after cooling.

[0014] The ball milling time in step S1 is 0.5 to 3 hours; the grinding balls are tungsten carbide; the mass ratio of the raw material to the grinding balls is 1:(3 to 5); the transition metal oxide (TMO S ) powder, boron carbide (B4C) powder, and carbon source powder have a molar ratio of 2:(1-1.5):(4.7-5); the added amount of the silicon dioxide (SiO2) powder is x Vol.% of the uniformly mixed powder, 0<x≤10.

[0015] The transition metal oxide (TMO) in step S1 S ) powder is WO3, ZrO2, TiO2 or HfO2, preferably WO3.

[0016] The pressure of the dry pressing compact in step S2 is 3-30 MPa; the insulation time is 1-2 h; the grinding is performed in an agate mortar, and the screening is performed through a 200-mesh sieve.

[0017] The pre-pressing pressure in step S3 is 3-30 MPa; the spark plasma sintering is carried out in a vacuum or argon protective atmosphere, and the sintering pressure is 10-30 MPa; the insulation time is 10 minutes.

[0018] The ball milling in step S1 is carried out using a high-energy ball mill, a vibrating ball mill, a planetary ball mill, a field-assisted mill, a plasma-assisted high-energy ball mill or a stirring ball mill.

[0019] The sintering in step S3 may be hot pressing sintering furnace sintering or pressureless sintering.

[0020] A transition metal boride bulk material prepared using the above method, wherein the transition metal boride bulk material is WB2, and has a density of 98.36% and a hardness of 24.9±0.48 Gpa, which is superior to the optimal WB2 ceramic material prepared by prior art (density 95.8%, hardness 24.3±0.36 Gpa).

[0021] The above-mentioned transition metal boride bulk materials are used in the fields of high-performance coatings, hydrogen catalysis, powder metallurgy, grinding and polishing, cutting tools, high-temperature resistant materials and wear-resistant materials.

[0022] Principle of the present invention:

[0023] B2O3 can form a eutectic glass phase B2O3-SiO2 with SiO2. According to the binary phase diagram of B2O3 and SiO2, the melting point of the B2O3-SiO2 glass phase can be adjusted by controlling the content of SiO2 in B2O3. The present invention utilizes this principle to add SiO2 to the transition metal boride to generate B2O3-SiO2 with B2O3 on the surface of the boride. By controlling the amount of added SiO2, liquid phase sintering is promoted, thereby improving the densification effect of the transition metal boride ceramics and improving the mechanical properties. For a specific transition metal boride powder, the control of the addition amount of silicon dioxide is the key to achieving high density. And it is applicable to all cases related to the sintering of transition metal boride ceramics.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] (1) The transition metal boride powder obtained by the present invention can obtain a powder with high yield and fine grains at a relatively low cost, and is suitable for large-scale industrial production.

[0026] (2) The present invention is to prepare a transition metal boride (TMB S) process, a small amount of silicon dioxide (SiO2) was added to synthesize the B2O3-SiO2 glass phase, which effectively refined the grains and prepared a submicron transition metal boride powder with good sintering properties. It can be used to prepare transition metal boride ceramics with high density and high hardness; the density of the sintered transition metal boride ceramics is 98%, and it still maintains high hardness under high load. It proves the role of a small amount of SiO2 in refining the particle size of WB2 powder and promoting the sintering of bulk materials.

[0027] (3) The transition metal boride powder prepared by the present invention can be used in related industrial fields such as high-performance coatings, hydrogen catalysis, powder metallurgy, grinding and polishing; the transition metal boride ceramics can be used in related industrial fields such as cutting tools, high-temperature resistant materials and wear-resistant materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD pattern of the tungsten diboride powder prepared in Example 1-2.

[0029] Figure 2 This is the SEM image of the tungsten diboride powder prepared in Example 1-2.

[0030] Figure 3 This is the powder particle size distribution diagram of the tungsten diboride powder prepared in Example 1-2.

[0031] Figure 4 This is the XRD pattern of the tungsten diboride bulk prepared in Example 3-4.

[0032] Figure 5 This is a SEM image of the cross-section of the tungsten diboride block prepared in Example 3-4.

[0033] Figure 6 This is a graph showing the hardness variation of the tungsten diboride block prepared in Example 3-4. DETAILED DESCRIPTION

[0034] The present invention is further described below with reference to specific embodiments, but they should not be construed as limiting the present invention.

[0035] The ball mill used in the following examples is a high-energy ball mill (U.S. SPEX Company, model 8000M). The raw materials used in the following examples are tungsten trioxide (WO3, purity 99.9%, particle size 500 nanometers, Shanghai Xiangtian Nanomaterial Co., Ltd., China), boron carbide (B4C, purity 99.9%, particle size 1 micron, Shanghai Xiangtian Nanomaterial Co., Ltd.), carbon black (purity 99.9%, particle size 30 nanometers, Cabot), and silicon dioxide (SiO2, purity 99.9%, particle size 1 micron, Shanghai Xiangtian Nanomaterial Co., Ltd.).

[0036] Example 1

[0037] 1. Weigh tungsten trioxide powder, boron carbide powder and carbon black powder in a molar ratio of 4:1.075:4.8 in an argon environment and place them in a tungsten carbide ball mill. Add six tungsten carbide grinding balls with a grinding ball size of 11m and a mass ratio of grinding balls to mixed powder of 4:1. Ball mill for one hour in an argon environment to obtain a uniformly mixed powder.

[0038] 2. The mixed powder obtained in step 1 is pre-pressed into a compact by a dry press, and then the block is placed in an atmosphere furnace and kept warm for one hour in a vacuum environment at 1400°C. After cooling with the furnace, the obtained loose block is broken into pieces, ground in an agate mortar and passed through a 200-mesh sieve to obtain tungsten diboride powder.

[0039] Example 2

[0040] 1. Weigh tungsten trioxide powder, boron carbide powder and carbon black powder in a molar ratio of 4:1.075:4.8 under argon environment, add silicon dioxide powder, and place them in a tungsten carbide ball mill. Add six tungsten carbide grinding balls with a ball size of 11m and a mass ratio of grinding balls to mixed powder of 4:1. Mill under argon environment for one hour to obtain a uniformly mixed powder. The amount of silicon dioxide powder added is 1Vol.%, 2Vol.%, and 3Vol.% of the uniformly mixed powder.

[0041] 2. The mixed powder obtained in step 1 is pre-pressed into a compact by a dry press, and then the block is placed in an atmosphere furnace and kept warm for one hour in a vacuum environment at 1400°C. After cooling in the furnace, the obtained loose block is broken up, ground in an agate mortar and passed through a 200-mesh sieve to obtain tungsten diboride powder with 1Vol.%, 2Vol.%, and 3Vol.% SiO2 added.

[0042] Figure 1 : is the XRD diagram of the fine-grained flaky tungsten diboride powder prepared in Example 1 and Example 2. Figure 1 It can be seen from the phase composition of the synthesized powder that the main phase of all samples of the powder after heat treatment at 1400℃ is WB2 type WB2 (P63 / mmc, ICCD PDF#43-1386). However, a small amount of tungsten trioxide phase appears, which is due to the insufficient reaction rate, resulting in insufficient oxide reaction and residual oxide. The silicon dioxide phase was not detected in the XRD spectrum, which is because the amount added is very small, and the detected diffraction peak intensity is very weak compared to the diffraction peak intensity of tungsten diboride.

[0043] Figure 2 and Figure 3 1 is a SEM image and a powder particle size distribution diagram of the fine-grained flaky tungsten diboride powder prepared in Example 1 and Example 2. Figure 2 It can be clearly seen that the addition of silicon dioxide powder can effectively promote the reduction of the particle size of tungsten diboride flake grains. Figure 3 From the powder particle size distribution diagram, it can be seen that the particle size distribution has decreased to varying degrees after adding silica powder, especially when 1 Vol.% SiO2 is added, the powder particle size is reduced from 0.43 microns when no addition is made to 0.29 microns.

[0044] Example 3

[0045] The tungsten diboride powder obtained in Example 1 was placed in a graphite mold and pre-pressed with 10 MPa, and then sintered in a spark plasma sintering furnace with a sintering pressure of 30 MPa. The sintering atmosphere was argon and the temperature was kept at 1600° C. for ten minutes. After cooling, the mold was demolded to obtain a tungsten diboride block.

[0046] Example 4

[0047] The tungsten diboride powders with 1 Vol.%, 2 Vol.%, and 3 Vol.% SiO2 added obtained in Example 2 were placed in graphite molds for pre-pressing respectively, and then sintered in a spark plasma furnace at a pressure of 30 MPa, with argon as the sintering atmosphere, at 1600°C for ten minutes. After cooling, the powders were demolded to obtain tungsten diboride blocks with 1 Vol.%, 2 Vol.%, and 3 Vol.% SiO2 added.

[0048] Figure 4 The XRD pattern of the tungsten diboride bulk prepared in Example 3-4 is as follows: Figure 4 It can be seen that the main phase of the tungsten diboride blocks after sintering at 1600°C is WB2 type WB2 (P63 / mmc, ICCD PDF#43-1386), and no diffraction peak of WO3 is detected in the XRD spectrum. This is because the residual WO3 in the powder is fully reacted in the spark plasma sintering furnace, so no diffraction peak of WO3 is seen.

[0049] Figure 5 The SEM images of the tungsten diboride block prepared in Example 3-4 show that when silicon dioxide is not added, a small amount of pores exist between the grains, and the density is 96.6%. When 1Vol.% SiO2 is added, the pores are significantly reduced, the grains are evenly distributed and tightly packed, and the density is 98.4%. When 2Vol.% SiO2 or 3Vol.% SiO2 is added, the pores between the grains are significantly increased, and the density is 95.2% and 97.0%, respectively.

[0050] Figure 6The hardness change diagram of the tungsten diboride block prepared in Example 3-4 under a load of 9.8N. It can be seen from the figure that when 1Vol.% SiO2 is added, the hardness of the tungsten diboride block increases from 23.1±0.95Gpa to 24.9±0.48Gpa, and after adding 2Vol.% SiO2 or 3Vol.% SiO2, the hardness of the tungsten diboride block is 23.7±0.61Gpa and 22.5±0.56Gpa.

[0051] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for promoting the densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that The steps include: S1. The following raw materials: silicon dioxide powder, transition metal oxide powder, boron carbide powder, and carbon source powder are weighed and canned under an argon environment, and grinding balls are added. The mixture is ball-milled under an argon protective atmosphere at room temperature to obtain a uniformly mixed powder; S2, dry-pressing the uniformly mixed powder obtained in step S1 into a compact by using a dry press, and keeping the temperature at 1300° C. to 1500° C. in a vacuum state for 0.5 to 2 hours, and after cooling with the furnace, grinding and sieving the obtained loose block to obtain a transition metal boride powder with added silicon dioxide; S3, placing the transition metal boride powder with added silicon dioxide obtained in step S2 into a graphite mold for pre-compression, curing and sintering by spark plasma sintering at 1500-1700° C. for 5-15 min, and obtaining a transition metal boride bulk material after cooling.

2. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The ball milling time in step S1 is 0.5 to 3 hours; the grinding balls are tungsten carbide; the mass ratio of the raw material to the grinding balls is 1:(3 to 5); the molar ratio of the transition metal oxide powder, boron carbide powder, and carbon source powder is 2:(1 to 1.5):(4.7 to 5); the amount of silicon dioxide powder added is x Vol.% of the uniformly mixed powder, where 0<x≤10.

3. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The transition metal oxide powder in step S1 is WO3, ZrO2, TiO2 or HfO2.

4. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The transition metal oxide powder in step S1 is WO3.

5. The method of promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide according to claim 1, characterized in that: The pressure of the dry pressing compact in step S2 is 3-30 MPa; the insulation time is 1-2 h; the grinding is performed in an agate mortar, and the screening is performed through a 200-mesh sieve.

6. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The pre-pressing pressure in step S3 is 3-30 MPa; the spark plasma sintering is carried out in a vacuum or argon protective atmosphere, and the sintering pressure is 10-30 MPa; the insulation time is 10 minutes.

7. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The ball milling in step S1 is carried out using a high-energy ball mill, a vibrating ball mill, a planetary ball mill, a field-assisted mill, a plasma-assisted high-energy ball mill or a stirring ball mill.

8. The method of claim 1 for promoting densification sintering of transition metal borides and improving their hardness by adding trace amounts of silicon dioxide, characterized in that: The sintering in step S3 may be hot pressing sintering furnace sintering or pressureless sintering.

9. A transition metal boride bulk material prepared by the method according to any one of claims 1 to 8, characterized in that: The transition metal boride bulk material is WB2, which has a density of 98.36% and a hardness of 24.9±0.48 Gpa.

10. Application of the transition metal boride bulk material according to claim 9 in the fields of high-performance coatings, hydrogen catalysis, powder metallurgy, grinding and polishing, cutting tools, high-temperature resistant materials and wear-resistant materials.

Citation Information

Patent Citations

  • Preparation method of densified zirconium boride-silicon carbide composite ceramic

    CN112500171A

  • Flaky tungsten diboride powder containing defects as well as preparation method and application of flaky tungsten diboride powder

    CN115385695A